Relative Concern: Pros and Cons and Lessons to be Learned - Hisam Kim (Korea Development Institute (KDI), 2014)
Individuals with a strong tendency to compare themselves to others are those who place the priority on work, position, and material goods; have a high degree of financial success; and tend to engage in overconsumption and conspicuous consumption. However, this relative concern was correlated with poorer health and low degrees of happiness and life satisfaction. In order for upward comparison to be a catalyst for self-development, fair competition must be ensured. Relative concern can be used to nudge people into socially desirable behaviors, but in order to increase the degree of happiness, it is necessary to counter the negative effects of social comparison and look after the quality of life to enable people to enjoy a balanced life. - Relative concern is a double-edged sword. It can have the positive effect of stimulating self-development, but it can also have a negative effect on happiness. - Around 36% of Koreans consider it important to compare their standard of living with people around them, while 25% think it is not important. - People who are inclined to relative concern tend to prioritize work and material values and have a goal-oriented mindset. - Individuals with a tendency for relative concern were also likely to exhibit herding and maximizing behavior, while their altruism tended to be limited to their children and their spouse. - For each one-point increase on the relative concern scale, monthly income went up by 29%, real estate value by 22%, and financial assets by 21%. - For each one-point increase on the relative concern scale, expenditures on high-priced durable goods such as automobiles went up by 42 %. - Individuals inclined to relative concern had high levels of anxiety, stress, depression, insomnia, and feelings of isolation, and they had low levels of happiness and satisfaction about their life as a whole. - For each one-point increase on the relative concern scale, happiness fell by a level commensurate with a 20 million won drop in household income. - Relative concern, which Respondents with a tendency for relative concern were more likely to attribute unhappiness to restrictions on upward mobility, the economic recession, decreasing material satisfaction, anxiety about security issues, and in particular an increase in relative deprivation. - Relative concern, which implies concern about other's opinions, can be used to lead people to make conspicuous donations and to reduce use of electricity through peer pressure. - As competition intensifies in a zero-sum game where success is narrowly defined, the positive effects of relative concern are reduced. - If upward comparison is to become a catalyst for development, the person being compared to must not be too far ahead; there must be a way to catch up with that person, and it must be possible to compete with them. - At present, most Koreans prioritize work and financial success. If they are to enjoy greater happiness, they need to achieve a balanced life in which consideration is also given to well-being in the domains of personal relationships, health, and the community. - Research into behavioral economics, which can reveal the characteristics of human psychology and behavior, has the potential to promote policy goals through non-coercive and inexpensive means.
Keywords: 330